Guardians of Innocence: Enhancing Legal Safeguards for Child Victims of Sexual Violence in Indonesia - Andriansyah, Aziz; Saraswati, Retno; Cahyaningtyas, Irma (Indonesia Law Review, 2023)
Sexual violence against children is a crime that is quite disturbing and needs to get attention in society. The implementation of child protection must meet the requirements, among others, by implementing the development of truth, justice and child welfare. Based on the provisions in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The basic rights of children who need adequate protection include the right to live, the right to develop, the right to protection, the right to participate and the right to education. Efforts to prevent sexual abuse in children can also be carried out by involving the participation of parents and the need for the involvement of law enforcement officials in handling cases of sexual abuse in children so that a child's perspective is expected to have a deterrent effect on perpetrators of crimes of sexual harassment. This research is a normative legal research using statutory and conceptual approaches. The government's steps in efforts to prevent sexual violence are by carrying out active campaigns to increase public awareness and need to strengthen the deterrent effect on convicts of sexual violence against children by not granting convicts rights, such as remission, parole, and clemency so that perpetrators do not repeat their action at a later time.